A Technical-Economic Assessment of Producing Hydrogen and Biofuels via Gasification of Biomass in Solar Hybridised Dual Fluidised Bed - Nguyet Ky Ngo; Tara Hosseini; Peter Ashman; Graham Nathan; Woei Saw (SolarPACES Conference Proceedings, 2024)
In this work, the techno-economic performances of three conversion pathways using an upstream solar hybridised dual fluidised bed (SDFB) for biomass gasification were assessed. The annual solar share % over the solar multiple range of 1.4-3.4 varies between 7-17%, with the CO2 emissions avoided relative to the non-solar case varying between 7%-23%, using representative solar viability location in Australia. The projected break-even price varies between 5.5-6.1 AUD/kg (3.8-4.25 USD/kg) for hydrogen, 1.1-1.2 AUD/kg (0.75-0.85 USD/kg) for methanol, and 1.5-1.7 AUD/L (1.1-1.2 USD/L) for liquid fuels over the analysed oversize level of 1.4 to 3.4 at thermal storage capacity designs with less than 1% solar dumping rate for base case scenario. Overall, the derived break-even price from the SDFB gasifier configuration is higher than that of the non-solar gasifier case, yet this is dependent on the cost of supplement heat supply and carbon credit